Case Report: Biliary hemorrhage by intrahepatic pseudoaneurysm and asymptomatic right coronary artery pseudoaneurysm in a patient with STAT3 hyper IgE syndrome - Fujita, Daiki; Ueki, Masahiro; Yamanaka, Hiroshi; Watanabe, Kota; Yakuwa, Satoshi; Manabe, Atsushi; Yamada, Masafumi (Frontiers in Immunology, 2025)
STAT3-hyper IgE syndrome (STAT3-HIES) is a primary immunodeficiency disorder caused by dominant-negative mutations in STAT3, leading to defects in Th17 cell differentiation, immune regulation, and tissue repair. Patients are susceptible to recurrent infections and vascular abnormalities, such as vasculopathy and pseudoaneurysms. While involvement of cerebral, bronchial, and coronary arteries has been reported, hepatic artery involvement is rare. We describe a 25-year-old woman with genetically confirmed STAT3-HIES who presented with biliary hemorrhage secondary to a ruptured hepatic pseudoaneurysm. Emergency transcatheter arterial embolization successfully controlled the hemorrhage, and the patient was discharged without complications. Systemic vascular screening revealed an asymptomatic right coronary artery dilation, necessitating medical management with statin therapy. This case highlights hepatic pseudoaneurysm as a rare but life-threatening vascular complication in STAT3-HIES. Given the potential for multi-organ vasculopathy, systemic vascular screening by contrast-enhanced CT or MRI is crucial for early detection and management. Further research is needed to elucidate the mechanisms underlying vasculopathy in STAT3-HIES and establish optimal screening strategies to improve patient outcomes.